2022
DOI: 10.1103/physrevb.105.064107
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Ta-Ta and Te-Te bonding leading to the commensurate charge density wave in TaTe4

Abstract: The origin of the charge density wave in TaTe 4 is discussed on the basis of a first-principles density functional theory analysis of the Fermi surface, electron-hole response function, phonon band structure of the average structure, and structural optimization of the modulated phase. Analysis of the band structure and Fermi surface of the average structure clearly proves that despite the presence of TaTe 4 chains in the crystal structure, TaTe 4 is in fact a 3D material as far as the electronic structure near… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…Finally note that an enhanced inter-chain coupling kills the 1D electronic divergence, as recently found in the calculation of the Lindhard response for TaTe 4 [219,220], a metallic system exhibiting a 2 × 2 × 3 CDW modulation [221] (see section 8.3). Although this solid is usually described as a tetragonal array of TaTe 4 chains, thus suggesting a pseudo-1D electronic structure, a careful analysis of the structure shows that the chains (along the c-direction) are tightly interconnected through Te … Te interactions.…”
Section: The Electron-hole Response In the Presence Of Amentioning
confidence: 52%
See 4 more Smart Citations
“…Finally note that an enhanced inter-chain coupling kills the 1D electronic divergence, as recently found in the calculation of the Lindhard response for TaTe 4 [219,220], a metallic system exhibiting a 2 × 2 × 3 CDW modulation [221] (see section 8.3). Although this solid is usually described as a tetragonal array of TaTe 4 chains, thus suggesting a pseudo-1D electronic structure, a careful analysis of the structure shows that the chains (along the c-direction) are tightly interconnected through Te … Te interactions.…”
Section: The Electron-hole Response In the Presence Of Amentioning
confidence: 52%
“…Two DFT studies of the CDW in TaTe 4 have been recently reported [219,220] providing clear evidence for a strong coupling scenario of the CDW. Guster et al [219] have shown that there is a strong overlap between the Ta 5d z2 and Te p bands leading to a FS that contains both strongly warped pseudo-1D and 3D components.…”
Section: Metal…metal Vs Chalcogen…chalcogen Interactions and Electron...mentioning
confidence: 94%
See 3 more Smart Citations